Initial impacts of forest management on forest floor greenhouse gas fluxes in hemiboreal coniferous forests on drained nutrient-rich organic soils - Samariks, Valters; Laiho, Raija; Jauhiainen, Jyrki; Butlers, Aldis; Čiuldienė, Dovilė; Lazdiņš, Andis; Kamil-Sardar, Muhammad; Schindler, Thomas; Soosaar, Kaido; Vigricas, Egidijus; Līcīte, Ieva (Elsevier, 2026)
As greenhouse gas (GHG) concentrations in the atmosphere continue to rise, legal frameworks are implemented internationally, nationally, and regionally to address ways to mitigate climate change. These frameworks emphasize the role of forests in sequestering carbon dioxide and the challenges in managing forests effectively amidst climate change and increasing timber demand. There is thus an urgent need for comprehensive understanding of soil GHG fluxes to plan forest-sector climate change mitigation strategies effectively. This study aims to evaluate the initial effects of various forest management types: regeneration cut, partial cut, commercial thinning, and a combination of commercial thinning and wood ash fertilization, on GHG exchange of forest floor (soil, litter layer, roots, above-ground parts of ground vegetation) in hemiboreal conifer-dominated forests with drained nutrient-rich organic soils. Forest management significantly influenced forest floor GHG fluxes through differences in soil temperature and soil water-table level (WTL). Forest floor total respiration that describes overall soil activity responded variably to different employed management types, while in intact forests (Control sites) it decreased with increasing stand age. Regeneration cut resulted in CH4 emissions due to higher WTL and reduced evapotranspiration, while other management types maintained the forest floor as a CH4 sink. N2O flux varied across the management types; however, the flux remained minor in all cases. Overall, partial cut exhibited the lowest GHG flux increase. While our study covers initial responses, longer-term studies are needed to fully evaluate the management impacts on drained nutrient-rich organic soils that have high potential for contributing to GHG fluxes.
Keywords: emissions; flux; forest management; soil respiration; efflux; sink